1995
DOI: 10.1111/j.1476-5381.1995.tb13253.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition by wortmannin of M‐current in bullfrog sympathetic neurones

Abstract: 1 The actions of wortmannin, an inhibitor of myosin light chain kinase (MLCK), on M-type potassium current of dissociated bullfrog sympathetic neurones have been examined. 2 The amplitude of M-current was measured by whole cell recordings from cells pretreated with wortmannin (0.01-10gM) or the wortmannin vehicle, dimethylsulphoxide (0.0001-0.1 vol%), for 30 min. Internal (recording pipette) solutions having three different pCa values (6, 7 and 8) were used for the measurements. 3 Irrespective of the pCa, M-cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
1

Year Published

1995
1995
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 21 publications
(17 reference statements)
1
7
1
Order By: Relevance
“…Our findings differ from those of a previous study in which wortmannin had a direct inhibitory effect on g M in BFSG neurons that was independent of the presence of agonist (Tokimasa et al, 1995). Differences in the nucleotide content of the internal solutions used in the two studies may provide an explanation for this disparity.…”
Section: Pip 2 Resynthesis and Recovery Of Agonist-induced G M Suppressioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Our findings differ from those of a previous study in which wortmannin had a direct inhibitory effect on g M in BFSG neurons that was independent of the presence of agonist (Tokimasa et al, 1995). Differences in the nucleotide content of the internal solutions used in the two studies may provide an explanation for this disparity.…”
Section: Pip 2 Resynthesis and Recovery Of Agonist-induced G M Suppressioncontrasting
confidence: 99%
“…Although this is suggestive of a channel block mechanism, the effect of ML-7 on g M did not exhibit any obvious voltage or use dependence (our unpublished observations). It therefore may reflect a bona fide action on myosin light chain kinase, an enzyme that has been reported to affect g M (Akasu et al, 1993;Tokimasa et al, 1995). Despite this, ATP still suppressed the g M that persisted in the presence of ML-7; more importantly, the time course of recovery of the response was changed little (Fig.…”
Section: Inhibition Of Pip 2 Resynthesis Slows Recovery From G M Suppressionmentioning
confidence: 94%
“…Several previous studies have suggested that I M is regulated by phosphorylation catalyzed by myosin light chain kinase. Application of myosin light chain kinase inhibitors decreases I M , whereas intracellular perfusion of catalytic subunits of myosin light chain kinase enhances I M (Akasu et al, 1993;Tokimasa et al, 1995). The result presented here, that ATP is required to prevent the rundown of I M , extends these findings to suggest that myosin light chain kinase-catalyzed phosphorylation events not only alter the amplitude of I M but may be required for the maintenance of I M .…”
Section: Discussionsupporting
confidence: 69%
“…Considering that inhibitors of MLCK may cause off‐target effects on action potential firings and voltage‐gated Ca 2+ channels (Tokimasa et al . ; Richards et al . ; Tokuoka and Goda ), we next studied effects of genetic down‐regulation of endogenous MLCK.…”
Section: Resultsmentioning
confidence: 99%